1989
DOI: 10.1002/j.1460-2075.1989.tb08581.x
|View full text |Cite
|
Sign up to set email alerts
|

p34cdc2 is located in both nucleus and cytoplasm; part is centrosomally associated at G2/M and enters vesicles at anaphase.

Abstract: The cdc2+ gene product p34cdc2 is located immunocytochemically in both the nucleus and cytoplasm of human cells. It is uniformly distributed throughout the cytoplasm and is irregularly distributed in the nucleus. Part of p34cdc2 is associated with the centrosome and centrosomal staining increases late in the cell cycle and at the onset of mitosis. This distribution is corroborated by cell fractionation which also indicates that slower migrating forms of p34cdc2 are found in isolated centrosomes and in Triton-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
216
3
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(237 citation statements)
references
References 35 publications
17
216
3
1
Order By: Relevance
“…Interestingly, more and more evidence is accumulating that the (maturing) centrosome could play a key role in the initial activation of Cyclin B-Cdk1. Immunocytochemically, a fraction of Cdk1 that is bound to Cyclin B was shown to localize to centrosomes during interphase (Bailly et al, 1989(Bailly et al, , 1992. Initially, this localization pattern was suggested to regulate centrosome functioning.…”
Section: Plk1 and Mitotic Entrymentioning
confidence: 99%
“…Interestingly, more and more evidence is accumulating that the (maturing) centrosome could play a key role in the initial activation of Cyclin B-Cdk1. Immunocytochemically, a fraction of Cdk1 that is bound to Cyclin B was shown to localize to centrosomes during interphase (Bailly et al, 1989(Bailly et al, , 1992. Initially, this localization pattern was suggested to regulate centrosome functioning.…”
Section: Plk1 and Mitotic Entrymentioning
confidence: 99%
“…The principal cell cycle regulatory enzyme in fission yeast is the cyclindependent kinase cdc2 ϩ , and its activity is required for entry into mitosis (Bailly et al, 1989;Alfa et al, 1990;reviewed in Forsburg and Nurse, 1991). There are, however, no putative modification sites for this enzyme in the Cut11p sequence.…”
Section: Regulation Of Cut11p Localizationmentioning
confidence: 99%
“…The spindle is constructed from microtubules (MT) 1 whose polymerization is nucleated by the centrosome (reviewed in Kellogg et al, 1994), which is known in fungi as the spindle pole body (SPB) (reviewed in Snyder, 1994). Although these two organelles are structurally distinct, genetic and biochemical approaches have identified several common components of centrosomes and SPBs, including ␥-tubulin (reviewed in Kellogg et al, 1994), CDC31/centrin (reviewed in Schiebel and Bornes, 1995), and p34 cdc2 (Bailly et al, 1989;Raibowol et al, 1989). Thus, analyses of SPBs have been informative about centrosomes in general.…”
Section: Introductionmentioning
confidence: 99%
“…This observation indicates that the preferential association of pp60 .... with the material surrounding the centrioles is lost following the breakdown of the nuclear envelope and the beginning of spindle formation. The p34 acz protein kinase, a major cell cycle regulatory kinase (for reviews see Dunphy et al, 1988;Murray, 1988;lee and Nurse, 1988;Gautier et al, 1988) has been shown to be a nuclear and cytoplasmic protein with a cell cycle-dependent accumulation at the centrosome (Akhurst et al, 1979;Bailly et al, 1989), although a strictly nuclear localization has been reported by others (Riabowol et al, 1989). This protein is capable in vitro of phosphorylating pp60 .... at the same sites as those phosphorylated in vivo during fibroblast mitosis (Chakalaparampil and Shalloway, 1988;Shenoy et al, 1989;Morgan et al, 1989).…”
Section: Localization Of Pp60 ~ In Premitotic and Mitotic C-src Overementioning
confidence: 99%